2022
DOI: 10.1021/acscentsci.2c00329
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Reactive Carbon Solutions into CO at Low Voltage and High Carbon Efficiency

Abstract: Electrolyzers are now capable of reducing carbon dioxide (CO 2 ) into products at high reaction rates but are often characterized by low energy efficiencies and low CO 2 utilization efficiencies. We report here an electrolyzer that reduces 3.0 M KHCO 3 (aq) into CO(g) at a high rate (partial current density for CO of 220 mA cm −2 ) and a CO 2 utilization efficiency of 40%, at a voltage of merely 2.3 V. These results were made possible by using: (i) a reactive carbon solution enriched in KHCO 3 as the feedstock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 48 publications
0
84
0
Order By: Relevance
“…CO 2 electrolyzers can be fed with a gaseous CO 2 feedstock or with “reactive carbon solutions” enriched with (bi)­carbonate ions. , In this study, we focus on the electrolysis of 3.0 M KHCO 3(aq) into CO (Figure ). , The distinguishing feature of “bicarbonate electrolyzers” is that H + supplied by the anode to the cathode through a membrane reacts with the bicarbonate feedstock to form CO 2 in situ (“ i -CO 2 ”) (eq ). , It is this i -CO 2 that is reduced into CO at the cathode surface (eq ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 electrolyzers can be fed with a gaseous CO 2 feedstock or with “reactive carbon solutions” enriched with (bi)­carbonate ions. , In this study, we focus on the electrolysis of 3.0 M KHCO 3(aq) into CO (Figure ). , The distinguishing feature of “bicarbonate electrolyzers” is that H + supplied by the anode to the cathode through a membrane reacts with the bicarbonate feedstock to form CO 2 in situ (“ i -CO 2 ”) (eq ). , It is this i -CO 2 that is reduced into CO at the cathode surface (eq ).…”
mentioning
confidence: 99%
“… , The distinguishing feature of “bicarbonate electrolyzers” is that H + supplied by the anode to the cathode through a membrane reacts with the bicarbonate feedstock to form CO 2 in situ (“ i -CO 2 ”) (eq ). , It is this i -CO 2 that is reduced into CO at the cathode surface (eq ). …”
mentioning
confidence: 99%
“…13 Zhang et al further designed a 500 μm buffer layer between porous Ag foam and Nafion membrane to inhibit the HER activity, which obtained a 71% FE CO at 100 mA/cm 2 . 16 The use of Ag-based catalysts during bicarbonate electrolysis led to a huge burden on the commercial application. As a result, the designed micro- structure of the catalyst (NaCl@Ni/Zn-6) can promote reactant mass transport, which enhances the local reactant concentration around the active sites and increases the electrochemical performance.…”
Section: Microstructure Optimization and Performance Enhancementmentioning
confidence: 99%
“…Typically, the energy requirements during CO 2 capture and separation account for >76% in a traditional postcombustion CO 2 capture system . Electrolytic bicarbonate conversion to fuels or value-added chemicals (e.g., CO, formate, and C 2 H 4 ) can bypass these energy-intensive processes (i.e., CO 2 desorption and compression), providing an alternative approach for the future commercial application. Previous life cycle assessments confirmed that electrolytic bicarbonate conversion to CO had a 1.93 net energy ratio, much lower than that of electrolytic gaseous CO 2 conversion to CO (6.19), highlighting the energy-efficient characteristics of the electrolytic bicarbonate conversion …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation